Risk factors, early and late postpartum complications of retained placenta: A case control study. (May 2019) - Zmora, Itay; Bas-Lando, Maayan; Armon, Shunit; Farkash, Rivka; Ioscovich, Alex; Samueloff, Arnon; Grisaru-Granovsky, Sorina
Abstract: Objectives: To identify risk factors and complications associated with 3 rd stage of labor removal of placental fragments (3 rd SRPF) by manual uterine revision under a strict protocol. Study design: Ten years retrospective register-based cohort study of vaginal deliveries. Women with 3 rd SRPF n = 3297 (exposed) and those without n = 97, 888 (non exposed) were compared. Main outcomes measures: (1) risk factors for 3 rd SRPF aOR (95%CI) (2) early (2a) and late (2b) maternal complications. Results: (1) Risk factors for 3 rd SRPF procedure were assisted reproductive technologies 2.20 (1.73–2.34), preterm delivery 2.53 (2.21–2.88), preeclampsia 1.66 (1.25–2.21) Multiple previous early pregnancy loss (>3) 1.40(1.19–1.66), VBAC 1.26(1.13–1.47) and epidural analgesia 1.56 (1.46–1.69). (2a) Early complications: puerperal fever 1.1% vs 0.3%, blood transfusion 9.0% vs. 0.5%, prolonged maternal hospitalization 21.0% vs. 11.4%, all P < 0.0001. Puerperal readmission was 0.819% in the 3 rd SRPF vs. 0.315% the control group, P < 0.0001. (2b) Late complications: retained placenta and hysteroscopy / D&C rates were significantly higher among the 3 rd SRPF vs. controls: 40.7% vs. 7.1%, 14.8% vs. 3.6% and 48.1% vs. 18.2%, respectively, all P < 0.0001. Conclusion: Uterine revision for 3 rd SPRF is associated with significant early and late maternal morbidity; should be considered discriminative of a population at risk and postpartum health care planning, beyond being a therapeutic intervention.